The star formation and dynamics of nearby galaxies - Mogotsi, Keoikantse Moses (Department of Astronomy, 2017)
A scaling relation between the surface density of star formation and gas in the disks of galaxies has become the basis of our understanding of extragalactic star formation on scales of hundreds of parsecs and larger. This is an empirical law but star formation is a complex process - the presence of gas at sufficiently high densities to collapse and form stars depends on a wide variety of physical processes. These processes can be thought of in terms of the stability of galaxy disks, which is a balance between the gravitational force and competing forces such as the outward force due to pressure. In this study I explore how star formation is related to galaxy dynamics in the central regions of galaxies. This is done by determining the dominant contributor to the inner dynamics of galaxies and developing star formation models based on self-regulating disks that maintain a constant sub-critical stability parameter. Stability parameters for a gas-only disk and a two- uid disk containing both gas and stars are considered. These models are tested in the central regions of a sample of galaxies with a wide range of Hi masses, sizes, morphologies and stellar masses. The analysis is performed using Hα integral field spectroscopy, R-band, narrowband Hα, and near-infrared photometry to determine the star formation rates and kinematics of the galaxies. In agreement with previous studies I find that the central stellar surface density is tightly correlated with the central velocity gradient, which traces the steepness of the inner gravitational well. The baryonic fractions found in the analysis suggest that baryons dominate the central density of most galaxies in the sample, but better constraints on these are needed to make more firm conclusions. There are correlations between the star formation surface density and velocity gradient, however the observed relations do not match predictions from the models. Tests suggest that the failure of the models is due to the implied stability parameters in the galaxy centers not being constant across the galaxy sample, and that the star formation laws used in the analysis may not hold over the full parameter space of the sample.